Dynamic assessment of the left main-left circumflex bending angle: Implications for ostial left circumflex artery in-stent restenosis after successful two-stent PCI. (1st May 2023) - Wang, Zhiqing; Yang, Junqing; Li, Chunming; Huang, Jiayue; Fezzi, Simone; Chen, En; Cai, Wei; Stankovic, Goran; Wijns, William; Chen, Lianglong; Tu, Shengxian
Abstract: Background: Two-stent techniques for percutaneous coronary intervention (PCI) on left main (LM) bifurcation (LMB) lesions are associated with an increased risk of in-stent restenosis (ISR) at left circumflex artery (LCx) ostium but the underlying mechanisms are incompletely understood. This study sought to investigate the association between cyclic change of LM-LCx bending angle (BALM-LCx ) and the risk of ostial LCx ISR following two-stent techniques. Methods: In a retrospective cohort of patients undergoing two-stent PCI for LMB lesions, BALM-LCx and distal bifurcation angle (DBA) were computed with 3-dimensional angiographic reconstruction. The analysis was performed both at end-diastole and end-systole, and the angulation change throughout the cardiac cycle was defined as the cardiac motion-induced angulation change (∆C Angle). Results: A total of 101 patients were included. The mean pre-procedural BALM-LCx was 66.8 ± 16.1° at end-diastole and 54.1 ± 13.3° at end-systole with a range of 13.0 ± 7.7°. Pre-procedural ∆C BALM-LCx > 16.4° was the most relevant predictor of ostial LCx ISR (adjusted OR 11.58, 95% CI 4.04–33.19; p < 0.001). Post-procedural ∆C BALM-LCx > 9.8° and stent-induced diastolic BALM-LCx change > 11.6° were also related with ostial LCx ISR. DBA was positively correlated with BALM-LCx and showed a weaker association of pre-procedural ∆C DBA > 14.5° with ostial LCx ISR (adjusted OR 6.87, 95% CI 2.57–18.37; p < 0.001). Conclusions: Three-dimensional angiographic bending angle is a feasible and reproducible novel method for LMB angulation measurement. A large pre-procedural cyclic change of BALM-LCx was associated with an increased risk of ostial LCx ISR following two-stent techniques. Highlights: The3-dimensional angiography-based bending angle analysis is feasible and highlyreproducible. A large pre-procedural cyclic change of BALM-LCx was associated with ostial LCx ISR following two-stent PCI. Post-procedural cyclic change of BALM-LCx and stent-induced diastolic BALM-LCx change were also related toostial LCx ISR.